Development of a framework to encrypt plaintext to ciphertext - Zheng, Dongmiao (Nanyang Technological University, 2021)
The Fully Homomorphic Encryption scheme is an evolvement from the Brakerski- Gentry-Vaikuntanathan (BGV) scheme. It is an asynchronous encryption scheme with the power to compute over encrypted data without knowing the secret key which is used for decryption. It is also a cryptosystem that allows arbitrary computation on ciphertexts. In traditional synchronous encryption scheme interfaces, it is extremely easy for the secret key to be stolen and also easy for ciphertexts to be decrypted due to the fact that encryption and decryption employs the same secret key on plaintexts and ciphertext. Additionally, computations on data can only be executed upon decryption. Therefore, there is a demand for a asynchronous encryption scheme to encrypt user input data. This project aims to develop a Graphical User Interface (GUI) which would in turn allow end-users to encrypt their data using both traditional Advanced Encryption Standard (AES and Fully Homomorphic Encryption (FHE) scheme. Data owners would also be able to notice some evident differences between the mentioned schemes. Next, this project would be made accessible for users to extract secret key, public key and ciphertext generated from the Graphical User Interface and proceed on to decrypt them using appropriate schemes. Lastly, after the encryption and decryption process, end-users would also be able to identify the most ideal parameters to be used on their data using the FHE scheme that would be based on the encryption performance shown on the GUI.